FACTORS INFLUENCING PARTICIPATION OF SMALLHOLDER RICE FARMERS IN THE ANCHOR BORROWER PROGRAMME (ABP) IN JIGAWA STATE, NIGERIA - Ali, M. A.; Garba, A.; Sani R. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The Study assessed the Factors Influencing Participation of Small Holder Rice Farmers in the Anchor Borrower Programme (ABP) in Jigawa State, Nigeria. Multi-stage sampling techniques were employed to select 258 smallholder rice farmers, 129 non-Anchor borrower program participant (NABP) and 129 Anchor borrower programme participant (ABP). Data were collected through the use of structured questionnaire and analysed using descriptive statistics, inferential statistics, and Tobit regression. The result shows that, majority of the respondents were in active age, 20-30years 73(28.3%); in term of marital status, most of respondents 55.8% were married, 69.8% of the respondents were male and most (72.9%) the respondents were literate. The result also revealed that (53.0%) of the respondents were members of the cooperative society. Average farming experience was 12 years and mean household size was 9 years with mean farm size of 1.5ha. The result of Tobit regression indicated that yield, extension visit, were positive and significant at P<0.01 and P<0.05 respectively in an influencing participation in ABP, it also shows that multidimensional poverty index, awareness was negative and significant at (P>0.01) and (P>0.01) in influencing participation in ABP in the study area. The major constraints to the participation of smallholder rice farmers in ABP as reported were, inadequate inputs, farmers level of education, land tenure system, and poor funding which were ranked 1st, 2nd, 2nd and 4th respectively. The study recommended that, Federal Government should consolidated on the gain of ABP in the state by increasing the fund for the programme in the State and make sure more smallholders rice farmers (SHF) benefit from the programme given that the programme has enhanced both income and outputs of the beneficiaries, Government and other stakeholders should encourage timely provision of inputs to ABP participants, Other agricultural and financial institutions in the State should streamline their procedure for securing loans in order to make it easy to farmers.